Peran Dinas Tenaga Kerja Kabupaten Temanggung Dalam Melindungi Pekerja Perempuan Yang Bekerja Malam Hari - Agung Pandu Winasis; Wida Astuti (Jurnal Discretie, 2020)
This study describes and examines the problems regarding the legal protection and supervision of woman workers who work at night by Labor Office of Temanggung Regency; as well as an obstacle when doing the legal protection and supervision of entrepreneurs who employ woman workers who work at night to Supervisor of Labor Office of Temanggung Regency. This research is empiric legal research which is descriptive.  In nature the data used in this research is primary data including primary and secondary legal materials. Data collection techniques used is interview at Labor Office of Temanggung Regency and Labor Supervision Unit of Magelang and also document study or library study used. Technical analysis is qualitative data analysis method with interactive model. The result shows the first one is that the used regulations of legal protection are Law No. 13 of 2003, Act of Indonesian Ministry of Labor and Transmigration No. KEP.224/MEN/2003, and Law No. 1 of 1970, protection done by seeing the rules about night workers in a companies at their Company Regulations and Collective Labor Agreement, as well as supervision is done by preventive and repressive supervision. The last one is there are some obstacles experienced when doing supervision specifically an internal obstacle and also external obstacle.